Munāsabah dalam Tafsir Al-Qur’an Al-Karim Karya Mahmud Yunus - Marzuki, Ahmad (Aphorisme: Journal of Arabic Language, Literature, and Education, 2024)
This paper reviews the discourse on munāsabah found in the Qur'anic exegesis by Mahmud Yunus. This monumental tafsir sparked discussion due to Mahmud Yunus' bold approach to interpreting the Qur'an. Munāsabah is a study within the Ulumul Qur'an (the sciences of the Qur'an) that holds aesthetic value in the process of revelation since the Qur'an was first revealed. It serves as a historical key to understanding the context of certain verses when they were revealed. This research explores various aspects, including the munāsabah present in Mahmud Yunus' tafsir. This research employs a qualitative method based on library research, combining two sources: the primary source in the form of Tafsir al-Qur'an al-Karim and secondary sources such as journals, blogs, or relevant literature. The results of this study reveal that the author identified elements of munāsabah based on Mahmud Yunus' theoretical framework. The first is munāsabah between one surah and another in the Qur'an (such as between Surah Al-Baqarah: 22 and Surah An-Nur: 43). The second is the munāsabah between the end of one verse and the beginning of the next (such as between the end of Al-Baqarah: 219 and the beginning of Al-Baqarah: 220).